ON THE ORIGIN OF RECENT VERTICAL MOVEMENTS OF THE EAST ASIATIC CONTINENT ISLAND SYSTEMS - Lyapishev A.M.; Soloviev V.N.; Sychev P.M.; Eremin G.D.; Zakharov V.K.; Semakin V.P. (My University, 1981)
Recent slow vertical movements in Sakhalin, Japan and Kamchatka are mainly the continuation of modern movements that began in the Quaternary and older periods. In many cases positive and negative Recent vertical movements coincide spatially with uplifts and troughs, respectively. In some cases Recent movements are not stable in their sign, but are influenced by short-period “pulsations”; their total meanings for long periods of time according to their sign correlate on the whole with modern structure forms, being expressed as a relief. Spatial distribution and configuration and also conjunction of the uplift and trough areas, accompanied by variations of gravity anomalies, are strongly similar with the character of rapid vertical movements, connected with Recent volcanic activity and earthquakes. This circumstance allows us to assume their common origin also, connected with supply of sialic material into the Earth's crust. Cross-sectional sizes of uplifts and wave lengths of vertical movements allow us to determine the depth of foci (zones), where concentrations of supplied sialic material occur. For the most part of structures with sizes up to 60–70 km these foci are distributed at the depths of 10–15 km. There are also structures with longer wave length, which are connected with the formation of zones of partial melting near the Moho discontinuity or in the upper mantle. The occurrence of such foci is confirmed in many cases by the presence of zones of increased electric conductivity and decrease of the elastic wave velocities in the Earth's crust and upper mantle. The vertical movements mentioned above, which are apparently associated with a step-like rise of magmas of different composition, formation and evolution of partial melting zones on different levels, are supposed to be a widely spread phenomenon.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная